2013
DOI: 10.1111/scs.12061
|View full text |Cite
|
Sign up to set email alerts
|

The third paradigm in labour pain preparation and management: the childbearing woman's paradigm

Abstract: In this paper, we are presenting a study within the third paradigm in labour pain preparation and management: the childbearing woman's paradigm - the first and second being the midwifery and the medical paradigm, respectively. Midwives can play a major role in working with women in their preparation and management of labour pain. In the future, more research has to be done to illuminate this essential part of the childbearing woman's paradigm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 60 publications
2
30
1
2
Order By: Relevance
“…The majority of women described positive aspects of their support throughout labour, particularly when continuity and continued reassurance was provided, whether this is in an explicit or implicit form. Interestingly this appeared consistent across the studies regardless of culture, religion, parity or context (Hallsdorsdottir and Karlsdottir, 1996;Gibbons and Thomson, 2001;Escott et al, 2004;Leap et al, 2010;Beigi et al, 2010;Rachmawati, 2012;Karlsdottir et al, 2014). Consequently it appears, despite the heterogeneity of participants across the studies, all women value continuous support to enhance coping ability.…”
Section: 'It Was Truly Amazing To See the Difference In Having A Midwmentioning
confidence: 69%
See 4 more Smart Citations
“…The majority of women described positive aspects of their support throughout labour, particularly when continuity and continued reassurance was provided, whether this is in an explicit or implicit form. Interestingly this appeared consistent across the studies regardless of culture, religion, parity or context (Hallsdorsdottir and Karlsdottir, 1996;Gibbons and Thomson, 2001;Escott et al, 2004;Leap et al, 2010;Beigi et al, 2010;Rachmawati, 2012;Karlsdottir et al, 2014). Consequently it appears, despite the heterogeneity of participants across the studies, all women value continuous support to enhance coping ability.…”
Section: 'It Was Truly Amazing To See the Difference In Having A Midwmentioning
confidence: 69%
“…Despite all studies providing information describing the characteristics of their sample, only one study explicitly reported the use of induction or augmentation during labour (Gibbons and Thomson, 2000). The strongest theme evident throughout the studies was the need for continuous, individualised support throughout the childbirth experience and the impact this had upon coping ability (Hallsdorsdottir and Karlsdottir, 1996;Gibbons and Thomson, 2001;Escott et al, 2004;Leap et al, 2010;Beigi et al, 2010;Rachmawati, 2012;Karlsdottir et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations